Pengaruh Pendapatan Asli Daerah, Pendapatan Transfer dan Pembiayaan Daerah terhadap Kinerja Keuangan Pemerintah Daerah Gerbang Kertosusila - Sofyan, Afis; Syaiful Akbar, Fajar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The”regional government's financial performance, which is still not at a good stage in the 2017–2021 period, as measured by the Gerbang Kertosusila regional government harmony ratio, is the background for this research. Original regional income, transfer income, and regional financing are elements that influence the financial success of regional governments. The aim of this research is to find out whether regional finances, local original income and transfer income have an effect on the financial performance of the Pintu Kertosusila regional government from 2017 to 2021. The data in this research was collected quantitatively through researcher observation. The research data was then analyzed in SPSS version 25.0 using multiple linear regression analysis techniques. Based on the results of this research, PAD (X1) has a positive impact on regional government financial performance, transfer income (X2) has a negative impact on regional government financial performance, and regional financing (X3) has no significant impact on regional government financial performance.